(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study was conducted during 1/9/2014 to 1/4/2015 in Najaf governorate ,Iraq to investigate the possible association of blood pressure, diabetes mellitus, anemia and body weight with ABO type. The data were obtained from 49 individual randomly. data Analyzing showed that high levels of incidence of hypertension at the O blood group reaching 14% ,while the incidence of anemia was highest percentage in type A and B with no significant differences .The results also showed high average of diabetes in type B with 29%, high average of body weight also recorded in type AB with 72.2%.